THE CORRELATION AMONG THE ELEVENTH GRADE STUDENTS’ LEARNING STRATEGIES, READING ATTITUDE, AND READING ACHIEVEMENT AT STATE HIGH SCHOOL 22 OF PALEMBANG - Ria Maya Lestari Manurung (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThe study is concerned with the correlation among the eleventh grade students’ learning strategies, reading attitude and reading achievement at state high school 22 palembang. In this study, 40 students of the eleventh grade students at state high school 22 of Palembang in academic year 2015/2016 were chosen as samples through cluster random sampling. This study applied correlational research design. The data were collected by using questionnaires and test and were analyzed by using Pearson Product Moment coefficient and multiple regression analysis. The result showed that there was positive correlation between language learning strategies and reading achievement (0.004 < 0.05); between reading attitude and reading achievement (0.028 < 0.05); between language learning strategies and reading attitude (0.006 < 0.05), and among language learning strategies, reading attitude and reading achievement ( 0.004 < 0.05)Key words: Language Learning strategies, Reading Attitude, readingAchievement